Learning English With Travel Blogs: A Genre-Based Process-Writing Teaching Proposal - Daniel Pascual (Profile: Issues in Teachers' Professional Development)
Current communication is increasingly computer-mediated, dynamic, dialogic, and global, so students should master new information, communication technologies, and digital genres, as well as acknowledge the global role of the English language. Thus, this paper aims to offer a teaching proposal, to be ideally implemented in the secondary education English as a foreign language classroom, on how to develop students’ communicative and digital competences based on a digital genre like the travel blog. First, a corpus of travel blogs was compiled, and the blogs’ communicative purposes and prominent linguistic and discursive features were identified. Next, different lesson plans were designed on the principles of communicative language teaching and task-based learning, together with the corpus-based results. Overall, students are expected to follow a process-writing approach that enables them to interact digitally in travel blogs.